Bad Kitty : party animal - Bruel, Nick (Bruel, Nick. Bad Kitty., 2025)
"While Puppy gets a BIG present and a very SPECIAL birthday breakfast, all Kitty can do is pop the balloons, topple the cake, and cause MAYHEM ... unless she can learn how to let Puppy have the spotlight"--